Evaluasi Pendidikan Islam Menghadapi Tantangan di Era Digital dan Artificial Intelligence - Ade Ripai; Siti Laelatul Badriah; Lia Agustin; Siti Sarah; Aida Ayu (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2026)
This research aims to examine the opportunities, obstacles, and strategies for integrating Artificial Intelligence (AI) in Islamic Religious Education, while maintaining a balance between technological progress and the fundamental values of Islamic teachings. Using a literature review method of both classical and modern references, this study analyzes changes in PAI teaching methods, media, and techniques. The results show that AI opens significant opportunities to improve learning quality through more personalized and flexible learning processes that align with the characteristics of today’s digital generation. Beyond facilitating access to and delivery of materials, AI integration can also strengthen students’ moral and spiritual development, ensuring that the essence of religious education is preserved amid modernization. However, AI implementation faces considerable challenges, including unequal technological infrastructure in remote areas, limited digital skills among educators, and ethical concerns regarding system bias that may conflict with Islamic principles of justice. Therefore, a comprehensive strategy is needed: synergy between Islamic scholars and technology experts, improved facilities and digital literacy, development of a curriculum that combines conventional and digital methods, and regulations that ensure ethical AI use. A gradual and dialogical approach is also essential to gain public acceptance.